The application of the free boundary condition to the problem of binary smelt crystallization - Kanischev, V.N.; Barannik, S.V. (Functional Materials, 2007)
The problem of impurity diffusion in the melt crystallizing at a constant velocity has been tried to solde by the method of integral functionals with unknows region of integration and free boundary condition. It has been shows that the conditions at the phase boundary are contradictive to each other within the frame of the simplest bidimensional model of solidification. The general problen of existence of a solution for the problem of binary melt solidification is considered.